Knowledge of Dental Pain Emergency in 45-59 Years Old Community in Cimahi with Clickdent Application - R Yuslianti, Euis; Widyasari, Ratih; R Damayanti, Vinsensia (ACTA Medical Health Sciences, 2024)
Dental pain is an unpleasant sensory and emotional experience due to tissue damage, and it is usually felt only in the form of a sensation and described as being different from other sensations. Clickdent is a dental application that can help users manage their dental health by providing information associated with dental health, tracking dental appointments and reminders, and connecting users with dental professionals. This study aimed to characterize the level of knowledge of dental pain emergencies and their management among individuals aged 45-59 using clickdent application. This research employed a descriptive research design with a survey method. The subjects of this study were the residents of Cimahi city, aged 45 to 59 years. The data was gathered through the completion of a questionnaire by the subjects. A total of 100 samples were collected using random sampling, and the obtained data was analyzed using descriptive analyses. The collected data were processed using Microsoft Excel in picture and table. The results showed that the respondent’s level of knowledge about dental pain emergencies had good result with an average of 64.62% answered correctly. It can be concluded that the community has good knowledge about dental pain emergency and the treatment. Clickdent applications can be useful tools to improve dental health management and facilitate access to dental professionals. DOI : 10.35990/amhs.v2n3.p122-129 REFERENCES Couve, E., Lovera, M., Suzuki, K., & Schmachtenberg, O. (2018). Schwann cell phenotype changes in aging human dental pulp. Journal of Dental Research, 1–3. Agusta, R. M. V., A. K. A. I., & Firdausy, M. D. (2014). Hubungan pengetahuan kesehatan gigi dengan kondisi. Mendali Jurnal, 2, 64–68. Franciscatto, G. J., Brennan, D. S., Gomes, M. S., & Rossi-Fedele, G. (2020). Association between pulp and periapical conditions and dental emergency visits involving pain relief: Epidemiological profile and risk indicators in private practice in Australia. International Endodontic Journal, 53, 887–894. Francisco, S. S., Suzuki, C. L. S., Lima, A. P. D. S., Maciel, M. C. R., & Murrer, R. D. (2017). Clinical strategies for managing emergency endodontic pain. RSBO, 13, 210–215. Fejerskov, O., Nyvad, B., & Kidd, E. (2015). Dental caries: The disease and its clinical management (3rd ed., pp. 155–169). Wiley-Blackwell. Woessner, J. (2018). Overview of pain: Classification and concepts. In Weiner’s Pain Management: A Practical Guide for Clinicians (pp. 35–48). Torabinejad, M., Walton, R. E., & Fouad, A. F. (2014). Endodontics: Principles and practice (5th ed., pp. 162–171). Elsevier. Hardadi, M. (2014). Gambaran tindakan pencabutan gigi tetap di Puskesmas Tinumbala Kecamatan Aertembaga Kota Bitung tahun 2013. e-GIGI, 2, 1–6. Siagian, K. V. (2016). Kehilangan sebagian gigi pada rongga mulut. e-CliniC, 4, 1–6. Bachtiar, Z. A. (2016). Perawatan saluran akar pada gigi permanen anak dengan bahan gutta percha. Jurnal PDGI, 65, 60–67. Wintarsih, O., Partosoedarmo, M., & Santoso, P. (2016). Kebocoran apikal pada irigasi dengan EDTA lebih kecil dibandingkan yang tanpa EDTA. Jurnal PDGI, 58, 14–19. Kuhnen, M., et al. (2009). Toothache and associated factors in Brazilian adults: A cross-sectional population-based study. BMC Oral Health, 9(7). https://doi.org/10.1186/1472-6831-9-7 Jaul, E., & Barron, J. (2017). Age-related diseases and clinical and public health implications for the 85 years old and over population. Frontiers in Public Health, 5, 1–7. Kementerian Kesehatan Republik Indonesia. (2019). Laporan hasil Riset Kesehatan Dasar (Riskesdas) Indonesia tahun 2018. Jakarta: Balitbangkes. Clauditiana, T. (2019). Gambaran perilaku kesehatan gigi dan mulut dengan indeks DMF-T pada lansia di UPT pelayanan sosial lanjut usia dinas sosial Binjai. Journal of Chemical Information and Modeling, 53, 3–12. Kristanti, C. M., & Hapsari, D. (2008). Persepsi nyeri gigi dan pola berobat, Susenas 2001. Jurnal Dental Indonesia, 14(1), 53–59. Purra, A. R., Sajad, M., Ahangar, F. A., & Farooq, R. (2018). Patient’s awareness and knowledge of the root canal treatment in Kashmiri population: A survey-based original research. International Journal of Contemporary Medical Research, 5, 2454–7379. Hargreaves, K. M., & Berman, L. H. (2016). Cohen’s Pathways of the Pulp (11th ed., pp. 706–722). Elsevier. Topazian, R. G., Goldberg, M. H., & Hupp, J. R. (2007). Oral and maxillofacial infections (4th ed., pp. 133–150). W.B. Saunders Company. Samaei, H., Weiland, T. J., Dilley, S., & Jelinek, G. A. (2015). Knowledge and confidence of a convenience sample of Australasian emergency doctors in managing dental emergencies: Results of a survey. Emergency Medicine International, 2015.